2003
DOI: 10.1182/blood-2002-10-3241
|View full text |Cite
|
Sign up to set email alerts
|

A new xenograft model for graft-versus-host disease by intravenous transfer of human peripheral blood mononuclear cells in RAG2-/- γc-/- double-mutant mice

Abstract: The safe application of new strategies for the treatment of graft-versus-host disease (GVHD) is hampered by the lack of a clinically relevant model for preclinical testing. Current models are based on intraperitoneal transfer of human peripheral blood mononuclear cells (huPBMCs) into NOD-SCID (nonobese diabetic-severe combined immunodeficient)/SCID mice. Intravenous transfer would be preferred but this has always been ineffective. We developed a new model for xenogeneic GVHD (X-GVHD) by intravenous transfer of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
155
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(173 citation statements)
references
References 38 publications
15
155
0
1
Order By: Relevance
“…Because serum hIL-21 can sustain as long as 7 days, hu-PBMC-BRG mice were sacrifi ced on day 7. In agreement with previous studies (van Rijn et al, 2003), the majority of engrafted cells in BRG mice were CD3 + T cells and CD19 + B cells (>90%, Fig. 2A).…”
Section: Human Il-21 Induced B Cell Engraftment and Robust Secretionsupporting
confidence: 93%
See 2 more Smart Citations
“…Because serum hIL-21 can sustain as long as 7 days, hu-PBMC-BRG mice were sacrifi ced on day 7. In agreement with previous studies (van Rijn et al, 2003), the majority of engrafted cells in BRG mice were CD3 + T cells and CD19 + B cells (>90%, Fig. 2A).…”
Section: Human Il-21 Induced B Cell Engraftment and Robust Secretionsupporting
confidence: 93%
“…Previous report showed that NK cells were very low in all compartments during the process of xenogeneic GVHD (van Rijn et al, 2003). And in our xenogeneic GVHD model, CD56 + CD3 -NK cells were almost absent in spleen of IL-21-treated group and control group on day 7.…”
Section: Protein Cellsupporting
confidence: 46%
See 1 more Smart Citation
“…pretransplant conditioning with sublethal irradiation [19,23,26,[32][33][34][35][36][37][38][39][40], (ii.) targeted reduction of murine natural killer (NK) cell activity with antibodies directed towards specific cell membrane markers (anti-asialo-GM1 [19,[33][34][35] or anti-CD122 [23,36,39]), (iii.)…”
Section: Introductionmentioning
confidence: 99%
“…targeted reduction of murine natural killer (NK) cell activity with antibodies directed towards specific cell membrane markers (anti-asialo-GM1 [19,[33][34][35] or anti-CD122 [23,36,39]), (iii.) targeted reduction of murine macrophages with clodronate-containing liposomes [37], (iv.) using newborn mice which lack a fully developed innate immune system [32], (v.) administration of interleukin-15 (IL-15) [38,40], and/or (vi.)…”
Section: Introductionmentioning
confidence: 99%